Land use change in an area surrounding an industrial estate : a case study of Surabaya Industrial Estate Rungkut (SIER), Indonesia - Damayanti, Rully (Curtin University, 2003)
This research aimed to investigate land use change in the area surrounding the Surabaya Industrial Estate Rungkut (SIER) in Surabaya, Indonesia. It was found that the industrial location has encouraged unplanned land use occupation, particularly the growth of informal sector activities. Analysis of government action sees the existence of the informal sector as a problem due to its non-taxpayer status, its illegal occupation of land and the poor environment and image it creates for the wider city. The government’s response to such a situation is to bulldoze the activities and associated development. The land use change that has occurred in the study area identified a precinct designated for residential uses that is currently occupied by commercial activity. This research identified the networks between the formal industrial activity in the industrial estate, and this commercial activity, both formal and informal. It also assessed the impact of the surrounding residential community on land use change. The study then analysed the planning approaches adopted that attempt to segregate land use between industrial and non-industrial uses and the attempts to limit the development of an informal, unplanned, unregulated land use. The study found that the current zoning regulations adopted from developed countries face many implementation problems particularly in providing for the accommodation of a large number of rural migrants. The appropriateness of land use segregation via zoning regulations to minimize the negative impact of industrial activity and to optimise the benefit of industrial land use networks was evaluated. The study recommends the creation of a more flexible and updated planning approach to land use change in Indonesia.